2015
DOI: 10.3389/fnhum.2015.00345
|View full text |Cite
|
Sign up to set email alerts
|

Inter-hemispheric integration of tactile-motor responses across body parts

Abstract: In simple detection tasks, reaction times (RTs) are faster when stimuli are presented to the visual field or side of the body ipsilateral to the body part used to respond. This advantage, the crossed-uncrossed difference (CUD), is thought to reflect inter-hemispheric interactions needed for sensorimotor information to be integrated between the two cerebral hemispheres. However, it is unknown whether the tactile CUD is invariant when different body parts are stimulated. The most likely structure mediating such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 78 publications
2
6
0
Order By: Relevance
“…Specifically, moving either the right or left hand during the observation of hand postures to-be-remembered reduces the memory span for such stimuli (Smyth and Pendleton, 1990). This is congruent with more recent studies that show bilateral activation of the hand area in the brain irrespectively of the stimulated hand (Rusconi et al, 2014;Tame and Longo, 2015;Tame et al, 2016Tame et al, , 2019.…”
Section: Memory For Action Reproductionsupporting
confidence: 86%
“…Specifically, moving either the right or left hand during the observation of hand postures to-be-remembered reduces the memory span for such stimuli (Smyth and Pendleton, 1990). This is congruent with more recent studies that show bilateral activation of the hand area in the brain irrespectively of the stimulated hand (Rusconi et al, 2014;Tame and Longo, 2015;Tame et al, 2016Tame et al, , 2019.…”
Section: Memory For Action Reproductionsupporting
confidence: 86%
“…By contrast, if sensory input and motor effector belong to different sides of the body, the information has to be integrated across hemispheres (crossed). In their study, the authors showed that the crossed-uncrossed difference in processing time was larger on the finger (2.6 ms) and forearm (1.8 ms) than on the forehead (0.9 ms; Tamè and Longo, 2015). The callosal connections and density of bilateral receptive fields (RFs) are consistent with such temporal difference.…”
Section: Integration Of Tactile Information Between the Two Sides Of mentioning
confidence: 94%
“…A recent study by Tamè and Longo (2015) provided behavioral evidence of the role of topographical organization of callosal connections in the integration of sensorimotor (i.e., touch) stimuli across the two sides of the body. Using a classical behavioral paradigm to quantify sensorimotor transfer between hemispheres, i.e., the Poffenberger paradigm (Poffenberger, 1912), the study revealed a modulation of the sensorimotor interhemispheric integration time as a function of the body part stimulated.…”
Section: Integration Of Tactile Information Between the Two Sides Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Tactile interactions between body sides change along the proximal-distal axis. A recent example of this is provided by Tamè & Longo (2015), who showed that sensorimotor integration is modulated by the body part stimulated, when using the Poffenberger paradigm (Poffenberger, 1912). This classic behavioural paradigm has been employed to quantify sensorimotor transfer between hemispheres.…”
Section: Interactions Between Tactile Stimuli On the Two Body Sidesmentioning
confidence: 99%